PENGARUH DESAIN PRODUK, CITRA MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK CONTAINER BERBAHAN PLASTIK PADA MASYARAKAT KOTA BANDAR LAMPUNG - Selvi Diah Pratiwi (Universitas Teknokrat Indonesia, 2023)
ABSTRACTBySelvi Diah PratiwiThis study aims to determine the effect of product design, brand image and price on purchasing decisions for plastic container products in the people of Bandar Lampung city. The population in this study were people using plastic containers in the city of Bandar Lampung, and the sample took the entire population using the nonprobability sampling method. The results showed that the product design and price variables partially had a positive and significant effect on the decision to purchase plastic container products in the Bandar Lampung City Community. However, brand image partially has no positive and significant effect on the decision to purchase container products made of plastic in the Bandar Lampung City Community. The results of the study also show that product design, brand image and price simultaneously have a significant effect on the purchasing decision of plastic container products in the Bandar Lampung City Community. Meanwhile, based on the coefficient of determination (R2) of 0.356 or 35.6%. This shows that 35.6% of the purchasing decision variable can be influenced by product design (X1), brand image (X2), and price (X3). While the remaining 64.4% is found in other variables that are not present or not examined in this study.Keywords: Purchase Decision, Product Design, Brand Image, Price, Plastic Container